In a community-based setting spondyloarthritis patients report higher levels of physical disability than chronic low back pain patients-results from EpiReuma.pt - Santos, Helena Carneiro (2023)
Publisher Copyright: © 2023, Sociedade Portuguesa de Reumatologia. All rights reserved.